The Extent to which Accounting Information is affected by Creative Accounting Methods - Abdullah, Omar Obaid (Journal of Economics and Administrative Sciences, 2025)
The paper focuses on investigating the impact on the Korean financial sphere, specifically Creative Accounting Practices (CAPs), by using the model in the paper, upon any type of AI. Included are various systems used for recording, monitoring, and reporting financial activities with AI as an intermingling agent for financial decision-making and resources management. The survey was carried out in Iraqi Carpet and Furnishing Company, where CAPs were plead to penance for their (mis-) deeds by artificially fast improvements in the appearance of the financial statements, thus eroding the trust in the adequacy and potency of the statements. The study referred to Miller's model in doing some sort of proper line-linking on the spotting as well as the interpretational section of the CAPs in company financial statements for the years 2018 to 2022. The finding asserted that CAPs in the financials of the company misled investors, sidelined its real financial performance, eroding confidence in AI, thus making the feasibility of the financial decision-making a moot front. It is crucial to establish more control and impart strict accounting standards and business ethics to ensure that there is a guarantee as to how they produce computerized financial information and mitigate the damage resulting from CAPs. This research sheds light on the understanding of the way CAP can distort the financial records and profoundly speaks for transparency in financial reporting. This research, thus, specifically conveys a message to the world about the importance of transparency and consists in writing financial reports while building trust and enforcement in ensuring accounting standards are adhered to. Last, but not least, the study lays firm emphasis on the entry of strict internal controls, instituting periodic audits, and the like, and imparting continued education to financial statement preparers to instill virtues of ethical practices in them. Through this, the study aims to widely inculcate in the spirit of honesty and accountability within most organizations, taming the risks associated with CAPs who would guarantee nothing but an accurate level of income and self-introduction of "authentic balances."